Contribution to the pollen morphology of Tragopogon (Asteraceae) in Turkey - Gültepe, Mutlu; Makbul, Serdar; Okur, Seda; Coşkunçelebi̇ Kami̇l (Phytotaxa, 2018)
The pollen morphology of 25 Tragopogon L. taxa (including four subspecies and four varieties) distributed in Turkey was studied under light and scanning electron microscopy. It was observed that pollen grains of the examined Tragopogon taxa are suboblate and oblate-spheroidal in shape, and 3-zonocolpororate with fifteen lacunae. The lenghts of the polar axes and equatorial axes range from 31.57 to 40.35 µm and 35.32 to 44.65 µm, respectively. Numerical analyses show that the length of equatorial axis and the pore length are the most valuable characters among nineteen palynological traits for separating the examined taxa. The general palynological characteristics of the examined taxa allow some taxonomical evaluations for the genus. However, the results of cluster and principal component analyses did not support the division of the genus at any subgeneric level; neither did the ligule colour, as reported in the literature.